Perbedaan komitmen Organisasi Karyawan Tetap dan Karyawan Outsourcing Pada PT. Bank Pembangunan Daerah œX - Jovan Januardha; Desi Nurwidawati (Universitas Negeri Surabaya, 2014)
The aim of this research was to examine the difference of organizational commitment level between regular and outsourcing employees in PT. Bank Pembangunan of œX, Syariah Division, Branch œXThis research is also to examine whether the organizational commitment of regular employees is higher than the outsourcing employees. There are one independent variables and one dependt variable, they are: a). status of employees, and b). organizational commitment. The sample of this research are employees of PT. Bank Pembangunan Daerah (BPD). The amounts of sample are 60 employees, 30 regular employees, and 30 others are outsourcing employees. The technique of data analysis in this research is a Independent Samples Test. Based on this Independent Sample Test Result is 6.101 on significant level of p = 0.000 (p<0.05). The result showed that there was a difference of organizational commitment between regular employees and outsourcing employees in PT. BPD. To conclude, the hyphothesis in this research is accepted.Abstrak: Penelitian ini bertujuan untuk mengethaui perbedaan tingkat komitmen organisasi antara karyawan tetap dan karyawan outsourcing pada PT. Bank Pembangunan Daerah (BPD) œX Divisi Syariah Cabang œX. Penelitian ini juga menguji apakah tingkat komitmen organisasi karyawan tetap lebih tinggi daripada karyawan outsourcing. Sampel penelitian ini adalah karyawan PT.BPD œX Divisi Syariah Cabang œX sebanyak 60 karyawan, yang terbagi menjadi 30 karyawan tetap dan 30 karyawan outsourcing. Teknik analisis data dalam penelitian ini adalah teknik independent sample test. Berdasarkan teknik analisis independent sample test diperoleh hasil uji t untuk varians sama sebesar 6, 101 dan taraf signifikasi (p) = 0,000 (p < 0,05). Hasil tersebut menunjukkan bahwa ada perbedaan komitmen organisasi antara karyawan tetap dan karyawan outsourcing pada PT. BPD œX Divisi Syariah Cabang œX . Dengan kata lain, hipotesis dalam penelitian ini diterima.